NOTES ON SOME GROWTH CHARACTERISTICS OF MIKANIA CORD AT A (BURM. F.) B.L. ROBINSON* - B.T. MERCADO (BIOTROPIA, 1994)
Mikania follows a sympodial dichotomy pattern of branching. Both stem (branches) and leaves give rise to new plants with relative ease. Internodes also root easily but do not give rise to new plants. Flower formation and seed germination are strongly influenced by light. Numerous seeds are produced but only few are filled; still fewer are the seeds that germinate. The period from early emergence to about the 3-leafed stage is most critical for survival of the new plant. Keywords: Mikania cordata, Growth, Weed physiology